Dynasties of India and beyond : Pakistan, Sri Lanka, Bangladesh - Malhotra, Inder (New Delhi : Dhaka : Harper Collins Publishers India, The University Press, 2004)
With special reference to India and Pakistan.
Includes bibliographical references (p. [337]-352) and index.
Keywords: Gandhi family; India -- Politics and government -- 1977-; Pakistan -- Politics and government -- 1971-